ANALISIS PERSPEKTIF GURU MATEMATIKA SMP DI KABUPATEN BOGOR TERHADAP STEM CHALLENGE SEBAGAI ASESMEN DALAM PEMBELAJARAN MATEMATIKA - Bustaren, Bill Chairy Rizki; Priatna, Nanang; Putri, Nurmala Setianing; Ulfa, Nadia (Universitas Nias Raya, 2025)
This study aims to analyze the perspectives of junior high school mathematics teachers in Bogor Regency regarding the implementation of the STEM Challenge as an alternative assessment in mathematics learning. This research uses a qualitative approach with a phenomenological method. Data were collected through open-ended questionnaires, in-depth interviews, and document studies. The results of the study reveal three findings: (1) teachers assess that the STEM Challenge is quite appropriate and has the potential to assess students' abilities, especially related to 21st century skills such as critical thinking, creativity, communication, and collaboration; (2) many teachers realize that conventional assessments (written tests) have limitations as they tend to focus only on cognitive aspects; and the last, (3), although the STEM Challenge is considered a good alternative assessment, teachers also expressed Challenges and obstacles in its implementation, including limitations in infrastructure, lack of learning time, and the need for adaptation for teachers and students. This research recommends the need for policy support, teacher training, and the provision of resources so that the STEM Challenge can be effectively implemented in order to make assessments in mathematics learning more contextual and meaningful.